The Ductch Colonial Policies on Religion and Education in the Dutch Indies (1889-1942) - Ading Kusdiana (UIN Sunan Gunung Djati, 2023)
This study aims to examine the inlandsch polietiek (indigenous politics) implemented by the Dutch Colonial Government during the colonial period in the Dutch East Indies in the 19th century. This study focuses on analyzing the religious and educational practices conducted by the Dutch Colonial Government throughout its rule. Utilizing historical research methods, this study found that the Colonial-Dutch Government adopted a fluctuating political strategy between neutrality and security to maintain its power. In the religious context, the Colonial Government tended to support Islam in its pure religious aspect, yet strived to prevent Islamic intervention in state administration affairs. Islamic education was compelled to follow an independent path, free from political influences. This conclusion is supported by the Besluit dated March 5, 1860, No. 10 f issued by the Dutch Colonial Government, and an analysis of Aqib Suminto's book,